Diseño de un modelo para el control y la fiscalización de los proyectos de obra pública en el ITCR - Araya-Segura, Luis Guillermo (Instituto Tecnológico de Costa Rica, 2013)
The present project aimed to establish an operational model to be applicable in the control and the supervision of public work contracts developed by the Oficina de Ingeniería of ITCR. To establish this model, developing and diagramming the process of public work execution were necessary to be carried out in that department. According to the rules of government contracting, a documentary research was conducted to determine the process of public works. Then, inside of this process was developed an inspection check; an applicable tool to facilitate the work of the project s inspectors. Also, another revision tool for administrative thread was proposed that were useful to the project coordinator. Finally, the operational model that allows the control and supervision of public works contracts developed in the Oficina de Ingeniería was established. From this project was concluded that in the Oficina de Ingeniería is developed a contract execution process made up of seventeen administrative threads. Finally, incorporating to the normal procedures the tools and the indicated processes were recommended in order to get an effective control and a supervision of public work contracts.
Proyecto de Graduación (Licenciatura en Ingeniería en Costrucción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2013.
Keywords: Contratación administrativa; Procesos administrativos; Modelo operacional; Inspector de proyecto; Análisis